New species, hosts, and records of Aporobopyrus Nobili, 1906 (Isopoda: Bopyridae: Pseudioninae) - An, Jianmei; Zhang, Yao; Chen, Xia; Paulay, Gustav (Zootaxa, 2026)
One new species and new records of four other species of the parasitic isopod genus Aporobopyrus Nobili, 1906 are reported, all with host records. Aporobopyrus asymmetricus sp. nov. is described infesting Petrolisthes teres Melin, 1939 in Australia, and it can be distinguished from congeners by the asymmetry lateral plates of pleomere 1 and having a pleotelson with distinct lateral plates. Aporobopyrus parvulus (Bourdon, 1983) is recorded from Kiribati, Line Islands, infesting Petrolisthes perdecorus Haig, 1981. Aporobopyrus aff. parvus Shiino, 1939 is recorded from the French Antilles, infesting Petrolisthes caribensis Werding, 1983; it is morphologically close to A. parvus from Japan. Aporobopyrus ryukyuensis Shiino, 1939 is reported from the Philippines infesting Petrolisthes tenkatei de Man, 1893. A new record of A. curtatus (Richardson, 1904) from Florida is also reported from Petrolisthes armatus (Gibbes, 1850). We review hosts and distributions of all Aporobopyrus, and provide a key to its species.